INVESTIGATION AND LEGAL ACTION TO FOREIGNERS WITHOUT PASSPORT IN INDONESIA TERITORY - Muhammad Arief Hamdi (Jurnal Ilmiah Kajian Keimigrasian, 2018)
Foreigners who enter and reside in the territory of Indonesia are regulated in the law, including travel documents of the Republic of Indonesia, visas, entry marks and residence permits, immigration controls, immigration administrative actions, and investigations. However, some foreigners who have been granted permission to continue to live in the territory of Indonesia. This is one of the things that must be followed up by immigration officials. Law enforcement that can be used in the form of Criminal Law or administrative legal action and the disabling factors that intentionally do not extend the residence permit, undergo criminal proceedings, undergo criminal law, and cannot be extended for emergency reasons. The research method is a type of normative research. The problem approach uses a legislative approach and a conceptual approach. Sources of legal material used are primary and secondary.